Successful simultaneous stenting of a pulmonary artery and vein in pulmonary vascular stenosis due to silicosis. Case report and literature review - Westhoff, M.; Hardebusch, T.; Litterst, P.; Breithecker, A.; Haas, M.; Kuniss, M.; Neumann, T.; Guth, S.; Wiedenroth, C. B. (Frontiers in Cardiovascular Medicine, 2023)
A 58-year-old patient was admitted to the emergency department due to severe respiratory insufficiency. Anamnesis revealed that the patient had experienced increasing stress dyspnea for a few months. Upon imaging, an acute pulmonary embolism was excluded, but peribronchial and hilar soft tissue proliferation with compression of central parts of the pulmonary circulation was found. The patient had a history of silicosis. The histology report showed tumor-free lymph node particles with prominent anthracotic pigment and dust depositions without evidence of IgG4-associated disease. The patient was administered steroid therapy and underwent simultaneous stenting of the left interlobular pulmonary artery and the upper right pulmonary vein. As a result, a significant improvement in symptoms and physical performance was achieved. The diagnosis of inflammatory or, in particular, fibrosing mediastinal processes can be challenging and important clinical symptoms must be taken into account, especially if the pulmonary vasculature is involved. In such cases, the possibility of interventional procedures should be examined in addition to drug therapy options.